Individual face- and house-related eye movement patterns distinctively activate FFA and PPA - Lihui Wang (Nature Portfolio, 2019)
The fusiform face area and parahippocampal place area respond to face and scene stimuli respectively. Here, the authors show using fMRI that these brain areas are also preferentially activated by eye movements associated with looking at faces and scenes even when no images are shown.